Innovative Application of Onion Extract to Improve the Quality of Tomato Fruit - Mayadewi, Ni Nyoman Ari; Gede Astawa, I Nyoman; Keswari Krisnandika, Anak Agung; Classia Sukendar, Ni Made (SOCA: Jurnal Sosial Ekonomi Pertanian, 2023)
Tomatoes are one of the daily necessities for people. In general, consumers favor tomatoes with few seeds. Therefore, there must be efforts made to improve the quality of tomatoes, one of which is to reduce the number of seeds, even if it is possible to make tomatoes without seeds (seedlessness).  By applying Gibberellic acid (GA) during the growth phase of tomato plants, it is possible to enhance tomato quality through technology. The application of GA to certain plants can reduce the number of tomato seeds and increase their sweetness. It is necessary to discover a way to use GA-containing natural ingredients to prepare for the high cost of synthetic GA. Onions are one of the natural ingredients that contain GA. Thus, this study aimed to examine the effect of applying onion extract as a source of GA to obtain the optimum concentration of onion extract that can improve the quality of tomato fruit. The experimental design utilized Randomized-Group Design with five different treatments: no spraying, spraying with 25%, 50%, 75%, and 100% onion extract. According to the findings, the application of onion extract improved the quality of tomato fruit. This condition is reflected by a decrease in the number and weight of seeds per fruit and an increase in the fruit's vitamin C content. Therefore, it is essential to conduct this research to produce inexpensive, high-quality tomatoes to sustain the economy and increase farmers' income